1997
DOI: 10.1002/jobm.3620370205
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of gluconate in Escherichia coli. The subsidiary system and the nature of the gntS gene

Abstract: The transport and phosphorylation of gluconate in E. coli occurs through two systems (GntI and GntII) which duplicate activities. bioH-asd deletion mutants do not grow on media with gluconate as sole carbon source because they lack the GntI system and do not express GntII. Although E. coli c177 is a delta (bioH-asd) mutant, it carries the pyrB linked mutation gnt177 that enables it to metabolize this substrate through inducible expression of the GntII system. Several gntS derivatives which are unable to grow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Genetic evidence for the presence of two systems for gluconate transport and phosphorylation was first provided by Bächi and Kornberg (2). Gluconate-fermenting pseudorevertants of E. coli HfrG6⌬MD2, a GntI deletion mutant (bioH-asd) which cannot grow on gluconate, were selected after extended incubation on minimal medium containing gluconate (11)(12)(13)22). The pseudorevertant strains were found to have induced a thermosensitive gluconate kinase and an alternative gluconate transporter when growing on gluconate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Genetic evidence for the presence of two systems for gluconate transport and phosphorylation was first provided by Bächi and Kornberg (2). Gluconate-fermenting pseudorevertants of E. coli HfrG6⌬MD2, a GntI deletion mutant (bioH-asd) which cannot grow on gluconate, were selected after extended incubation on minimal medium containing gluconate (11)(12)(13)22). The pseudorevertant strains were found to have induced a thermosensitive gluconate kinase and an alternative gluconate transporter when growing on gluconate.…”
Section: Discussionmentioning
confidence: 99%
“…A mutation affecting the subsidiary gluconate transporter was designated gntS (2), but it was never proven whether the gntS locus is a structural or regulatory gene, although it has been suggested that the gntS product positively controls expression of idnK (gntV) (2,11,13). Recent evidence apparently confirms the location of gntS upstream of fbp in the 95-min region and further supports the conclusion that gntS is a regulatory locus (12). However, examination of the genomic sequence in the 95-min region does not provide any further insights into the nature of gntS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both systems are transcriptionally regulated, i.e., induced by gluconate and repressed by glucose (9,58,60). In E. coli, another subsidiary gluconate system (GntII) has been previously described (30), but it is now considered the catabolic pathway for L-idonate where D-gluconate is an intermediary (4); the idn idonate operon (the former GntII) is repressed by a regulatory protein (IdnR) and globally repressed by the carbon source (5).…”
mentioning
confidence: 99%